2008
DOI: 10.1523/jneurosci.5607-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Odor Modulates Thalamocortical Connectivity in the Human Brain

Abstract: It is widely assumed that the thalamus is functionally irrelevant for the sense of smell. Although animal studies suggest that the mediodorsal (MD) thalamus links primary olfactory (piriform) cortex to olfactory neocortical projection sites in orbitofrontal cortex (OFC), this transthalamic route is regarded to be inconsequential, particularly compared with a direct monosynaptic pathway linking piriform cortex and OFC. In this study, we combined functional magnetic resonance imaging with novel effective connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
155
2
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(174 citation statements)
references
References 57 publications
14
155
2
3
Order By: Relevance
“…PCG including perirhinal and entorhinal cortex is considered as the piriform cortex and accepts olfactory afferent from olfactory bulb via olfactory tract, and then projects to olfactory neocortical projection sites in the orbitofrontal cortex (OFC) [33,34,35], while OFC, as the secondary olfactory cortex, is involved in more advanced processing of smell by integrating olfactory afferent information, taste, visual and visceral sense via hypothalamic dorsomedial nucleus [34,36]. The order of involvement of PCG and OFC is consistent with the projection pathway of olfactory processing [22,33], and with the hypothesis of the caudorostral pathological process in PD [3,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCG including perirhinal and entorhinal cortex is considered as the piriform cortex and accepts olfactory afferent from olfactory bulb via olfactory tract, and then projects to olfactory neocortical projection sites in the orbitofrontal cortex (OFC) [33,34,35], while OFC, as the secondary olfactory cortex, is involved in more advanced processing of smell by integrating olfactory afferent information, taste, visual and visceral sense via hypothalamic dorsomedial nucleus [34,36]. The order of involvement of PCG and OFC is consistent with the projection pathway of olfactory processing [22,33], and with the hypothesis of the caudorostral pathological process in PD [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that progressive atrophy of the piriform cortex and OFC correlated with the impairment of olfactory detection function, while atrophy in right OFC correlated with olfactory identification dysfunction, suggesting that piriform cortex and OFC might be involved in different roles of the olfactory process. Previous studies showed that the direct pathway of projection from piriform cortex to olfactory OFC serves as a quick and sensitive detection of odor, while the indirect circle between piriform cortex and OFC with a discriminative capacity and the feedback connections from OFC involved with cognitive factors, such as attention, expectation, and memory [33,34,37,38]. Meanwhile, a study of combining functional magnetic resonance imaging, peripheral autonomic recordings, and olfactory psychophysics showed that right OFC is a central substrate for human olfactory consciousness [39].…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory stimuli are processed in at least two different anatomical ways. Pure olfactory odours such as vanillin or phenylethanol are processed in the olfactory bulb (sensitivity, discrimination and filtering), primary olfactory cortex comprising the piriform cortex (somatosensory input of the sniff [10] , habituation effects [11] ), thalamus (awareness of odours [12] ), hippocampus and amygdala (emotion and memory processing [13] ), and orbitofrontal cortex (e.g. identification, discrimination [13] ) [14] .…”
mentioning
confidence: 99%
“…However, several lines of evidence point to an indirect involvement of the mediodorsal (MD) thalamus in the sense of smell [4][5][6][7][8][9]. In contrast, the role of the ventrolateral (VL) thalamus in olfaction is unclear at present.…”
Section: Introductionmentioning
confidence: 99%